Development of Interactive Learning Media for Software Engineering Subject Chapter Process Modeling in Higher Education - Sari, Nadia Roosmalita (Letters in Information Technology Education (LITE), 2020)
The software development process model or what is commonly called SDLC (Software Development Life Cycle) is one of the Software Engineering (RPL) course materials in the Information Engineering Education (PTI) undergraduate study program where one of the competencies is understanding and knowing the concepts of device engineering software that can be applied in the software development life cycle which is summarized in the material for the SDLC software development process model. This material is the initial material that must be mastered by students to develop quality software. The use of interactive and interesting computer assisted learning media is expected to help the stages of the student learning process properly. This requires an interactive learning multimedia application. The purpose of this research is to develop interactive learning media as an alternative to independent learning tools to assist students in mastering the Software Development Process Model (SDLC) material for students and to find out the feasibility of multimedia application products for learning the Software Development Process Model (SDLC). The research and development methodology used in this research is Research and Development (R&D) with Borg and Gall's development steps which include: (1) Research and data collection; (2) Planning; (3) Development of product drafts; (4) Initial field trials; (5) Revision of trial results (6) Field trials; (7) Product improvement; (8) Field implementation test; (9) Completion of the final product; and (10) Dissemination of implementation. This methodology covers all matters relating to development to produce quality interactive learning media software. Based on the trials, the results obtained were 90.63% from media experts, 98.08% from material experts, 85.46% from initial field trials, 84.56% from field trials, and 86.27% from field implementation trials. The average value obtained is 89% based on the results of the overall data analysis. The conclusion of this research is that the development of multimedia applications for learning the Software Development Process Model (SDLC) is feasible as an independent learning medium. The product produced in this development research is a multimedia application for learning flash-based software development process (SDLC) models.